THE MICRO-AND MACRO LEVEL INSTRUMENTS OF FINANCIAL CONSUMER PROTECTION IN HUNGARIAN LAW - Nagy, Zoltán; Somsák, Szilvia (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
The study deals with the legal questions of Hungarian consumer protection but in its assumptions, it concerns wider problems of other states’ practice of law. Concerning the definition of financial consumer, the authors call out the contentious fields of the whole area of law while sketching some solutions of the Hungarian regulation. The study puts a great emphasis on the consumer protectionist role and the tools of the supervision, underlining the newly regulated macroprudential instruments. Based on experiences, there is a need for softening the regulation of financial consumer protection, as long as it is an important, not just an individual-related question.